Evaluasi Normatif Dispensasi Perkawinan Pasca Undang-Undang Nomor 16 Tahun 2019 dalam Perspektif Maqāṣid Al-Syarī‘Ah: Studi Kasus di Pengadilan Agama Bima: Normative Evaluation of Marriage Dispensation Post-Law Number 16 of 2019 from the Maqāṣid Al-Sharī‘Ah Perspective: A Case Study at the Bima Religious Court - Putri Rahyu; St Maryam; Suci Mulyati; Salmiati; Anggar Putra (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2026)
This study examines the rising number of marriage dispensation applications at the Bima Religious Court as an indication of the ineffectiveness of existing legal policies in reducing child marriage rates. The purpose of this research is to identify the factors contributing to the increase in dispensation requests and to analyze the implementation of the policy from an Islamic legal perspective by assessing its conformity with the principles of maqāṣid al-Sharī‘ah, particularly the protection of life (ḥifẓ al-nafs), intellect (ḥifẓ al-‘aql), and lineage (ḥifẓ al-nasl). This research employs a juridical-normative approach with qualitative descriptive analysis based on literature studies, court decisions, and limited interviews with judicial officers. The findings reveal that the surge in dispensation applications is driven by social, cultural, and economic factors as well as low legal awareness within the community. From the perspective of maqāṣid al-Sharī‘ah, the granting of a marriage dispensation is permissible only under urgent circumstances that ensure greater public benefit and prevent potential harm, thus requiring judges to apply strict and proportional considerations. This study recommends strengthening legal awareness, tightening the criteria for granting dispensations, and enhancing collaboration among judicial institutions, local governments, and communities to ensure that Islamic family law policies operate fairly and remain oriented toward child protection.